Synergy of Accreditation and CAE Designation (Journal of The Colloquium for Information Systems Security Education, 2020)
One of the impediments to applying for the NSA/DHS Center of Academic Excellence in Cyber Defense designation is the fear that it will require a great change to the curriculum or may negatively impact international functional accreditations. This paper provides lessons learned while preparing to apply for this designation and enhancing our international ABET (computer science) and AACSB (business) accreditations. We found synergy between the new cybersecurity requirements for accreditation and CAE designation. Additional benefits of CAE designation include standards which help design, build, market and assess strong, well-defined cybersecurity programs in both computer science and business, each of which caters to a different audience of students and future employers. Finally, the CAE designation requires collaboration inside and outside the University, encouraging an active outreach to other programs. All of these benefits work in concert with the ABET and AACSB accreditations, which explicitly require an internationally recognized curriculum that is taught by experts in their field and regularly assessed.
Keywords: CAE; ABET; AACSB; accreditation; cybersecurity